Geographic variation in the treatment of non-ST-segment myocardial infarction in the English National Health Service: a cohort study. Issue 7 (12th July 2016) - Dondo, T B; Hall, M; Timmis, A D; Yan, A T; Batin, P D; Oliver, G; Alabas, O A; Norman, P; Deanfield, J E; Bloor, K; Hemingway, H; Gale, C P
Abstract : Objectives: To investigate geographic variation in guideline-indicated treatments for non-ST-elevation myocardial infarction (NSTEMI) in the English National Health Service (NHS). Design: Cohort study using registry data from the Myocardial Ischaemia National Audit Project. Setting: All Clinical Commissioning Groups (CCGs) (n=211) in the English NHS. Participants: 357 228 patients with NSTEMI between 1 January 2003 and 30 June 2013. Main outcome measure: Proportion of eligible NSTEMI who received all eligible guideline-indicated treatments (optimal care) according to the date of guideline publication. Results: The proportion of NSTEMI who received optimal care was low (48 257/357 228; 13.5%) and varied between CCGs (median 12.8%, IQR 0.7–18.1%). The greatest geographic variation was for aldosterone antagonists (16.7%, 0.0–40.0%) and least for use of an ECG (96.7%, 92.5–98.7%). The highest rates of care were for acute aspirin (median 92.8%, IQR 88.6–97.1%), and aspirin (90.1%, 85.1–93.3%) and statins (86.4%, 82.3–91.2%) at hospital discharge. The lowest rates were for smoking cessation advice (median 11.6%, IQR 8.7–16.6%), dietary advice (32.4%, 23.9–41.7%) and the prescription of P2Y12 inhibitors (39.7%, 32.4–46.9%). After adjustment for case mix, nearly all (99.6%) of the variation was due to between-hospital differences (median 64.7%, IQR 57.4–70.0%; between-hospital variance: 1.92, 95% CI 1.51 to 2.44; interclass correlation 0.996, 95% CI 0.976 to 0.999). Conclusions: Across the English NHS, the optimal use of guideline-indicated treatments for NSTEMI was low. Variation in the use of specific treatments for NSTEMI was mostly explained by between-hospital differences in care. Performance-based commissioning may increase the use of NSTEMI treatments and, therefore, reduce premature cardiovascular deaths. Trial registration number: NCT02436187.